Asymptomatic and Unnoticed Intra-articular Screw Over 18 Years after Fracture of the Posterior Wall of the Acetabulum – A Question of Stability? - Audretsch, Christof K.; Schmidutz, Florian; Küper, Markus Alexander (The Journal of Hip Surgery, 2024)
Fractures of the posterior wall of the acetabulum occur in a frequency of 25–30%. Multifragmentary fractures involving 40–50% of the acetabular surface, the quality of reduction as well as involvement of cartilage and acetabular labrum are considered to have an impact on the development of a reduced posterior stability of the hip joint. This results in a shift of the main weight bearing area with development of a posttraumatic osteoarthritis. In the presented case, a 42-year old male patient was operated on 18 years ago due to a posterior acetabular wall fracture. Retrospectively, one of the screws was located partially intraarticular. However, the patient was asymptomatic over the 18-year period. The first consultation was due to unspecific symptoms of osteoarthritis of the right hip joint especially during flexion and external rotation. Due to only mild radiological signs of osteoarthritis, we indicated only the removal of the intraarticular screw. The symptoms postoperatively switched to a feeling of instability, so a total hip arthroplasty was performed. Since the operation, the patient is asymptomatic regarding the hip joint. The intraarticular screw seemed to stabilize the hip joint. This case demonstrates the importance of a good posterior guidance for the stability of the hip joint on one hand. On the other hand, it demonstrates the minor stress load of the posterior acetabular region, especially after fracture of the posterior wall. Therefore, a good posterior guidance should be one major aim of treatment of posterior acetabular wall fractures.
Keywords: acetabular fracture; microinstability; acetabular labrum; posttraumatic osteoarthritis